Advanced Materials and Technologies in Nanogenerators - Wen, Zhen; Guo, Hengyu; Wang, Longfei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint discusses the various applications, new materials, and evolution in the field of nanogenerators. This lays the foundation for the popularization of their broad applications in energy science, environmental protection, wearable electronics, self-powered sensors, medical science, robotics, and artificial intelligence.